Legal Consequences of Delaying the Obligation to Repay Home Ownership Loans by Debtors Affected by the Covid-19 Pandemic : (Study at PT. Bank Tabungan Negara Syariah Banda Aceh) - Muhammad Syauqie Alihamna (Locus Journal of Academic Literature Review, 2022)
The government has declared the Covid-19 pandemic to be an emergency rather than a natural disaster based on Presidential Decree No. 12 of 2020, which has a very detrimental impact on the debtor, especially Home Ownership Credit debtors because it is unavoidable and unpredictable. The government through the Financial Services Authority issued POJK 11 / POJK.03 / 2020 concerning National Economic Stimulus as an effort to save the economy in the form of providing credit relaxation due to the co-19 pandemic. Therefore, research was conducted to find out and analyze the legal consequences of postponing the obligation to repay mortgage loans by debtors affected by the co-19 pandemic. The results of the study found that the legal consequences of granting credit delays or home ownership credit financing at Bank BTN Syariah Banda Aceh are changes in the agreement between the creditor and the debtor in terms of the implementation of the rights and obligations of the parties to the credit agreement, but the credit agreement is not canceled or canceled.